New insights into transfusion-related iron toxicity: Implications for the oncologist. (March 2016) - Porter, John B.; de Witte, Theo; Cappellini, M. Domenica; Gattermann, Norbert
Highlights: Transfusional iron overload and its consequences are increasingly recognized in MDS. Evidence suggests iron overload affects clonal evolution and progression to AML. Pre-existing iron overload can also influence HSCT outcomes. Appropriate monitoring of body iron levels can help reduce iron-related toxicity. Prevention of organ and bone marrow damage may improve clinical outcomes. Abstract: Iron overload is a potentially life-threatening consequence of multiple red-blood-cell transfusions. Here, we review factors affecting excess iron distribution and its damage to specific tissues, as well as mechanisms of oncogenesis by iron. Although consequences of transfusional iron overload are best described in thalassemia major and related inherited anemias, they are increasingly recognized in acquired conditions, such as myelodysplastic syndromes (MDS). Iron overload in MDS not only impacts on certain tissues, but may affect the clonal evolution of MDS through generation of reactive oxygen species. Iron overload may also influence hematopoietic-stem-cell-transplantation outcomes. Novel MRI methods for assessing body iron have impacted significantly on outcome in inherited anemias by allowing monitoring of iron burden and iron chelation therapy. This approach is increasingly being used in MDS and stem-cell-transplant procedures. Knowledge gained from managing transfusional iron overload in inherited anemias may be translated to general oncology, with potential for improved patient outcomes.